The incidence of basal cell carcinoma in Croatia : an epidemiological study - Celić, Dijana (Array, 2009)
Summary: The aim of the study was to investigate the basal cell carcinoma (BCC) incidence in Croatia in the 2003-2005 period. Data were collected from University Department of Dermatology and Venereology, Zagreb University Hospital Center and National Cancer Registry. The age-specific incidence rate and age-standardized incidence rate were calculated per 100,000 inhabitants according to the latest population census in Croatia from 2001. In the study period, there were 7,244 BCC cases (3,519 men and 3,725 women) in Croatia. The crude incidence rate for the Croatian population of 100,000 was 54.9 for men and 53.9 for women. The age-standardized incidence rate (adjusted for the world standard population) was 33.6 for men and 24.5 for women. The head and neck were almost exclusive localizations of BCC. The highest BCC incidence was recorded in Zadar County. The incidence of BCC was high in both littoral and inland counties of Croatia. Study results will serve as reference figures on studying the trend of BCC incidence in Croatia and Europe in the forthcoming years